Overview on Single Image Shadow Removal Using Different Techniques - Veena, Namde; Bhagate, Suhas B; Darbastwar, Smita S (International Journal of Computer Sciences and Engineering, 2018)
Shadow in the image degrades the quality of the image. So it is necessary to remove the shadow from the image. The detection of shadow and removal of the shadow from the images can be done through many different methods like reintegration method, cubic spline etc. The shadow in the image can be detected through user-assisted method that uses Support Vector Machine (SVM) and Markov Random Field (MRF) methods. Shadow from single image is removed using 3D intensity surface modelling to preserve texture without any loss in image. Using 3D intensity surface modelling method the accuracy can be increased i.e., the exact texture can be recovered in the shadow region after the shadow removal as compared to previous methods.